Reputation-based Wi-Fi deployment. - Salem, Naouel Ben
Wi-Fi networks have a very strong potential: They are easy to deploy, they use unlicensed frequencies and they provide internet connectivity that is several times faster than by cable modem. However, two major problems still need to be solved: the lack of a seamless roaming scheme and the variable quality of service experienced by the users. The reputation-based solution presented in this paper solves both problems: It allows a mobile node to connect to a foreign Wireless Internet Service Provider (WISP) in a secure way while preserving its anonymity and it encourages the WISPs to provide the users with good QoS. We analyze the robustness of our solution against various attacks and we prove by means of simulations that our reputation model indeed encourages the WISPs to behave correctly. We also propose a simple mechanism that allows the WISPs to predict the QoS they are able to offer to the (mobile) clients.
Keywords: Computer Systems Organization; Computer communication networks; Network architecture and design; Wireless communication; Local and wide area networks; Design; Experimentation; Measurement; Performance